ADSORPTION OF Am-241, Cs-137 AND Sr-90 RADIONUCLIDES WITH BENTONITE-HUMIC ACID IMMOBILIZED YIELD - Kris Tri Basuki; Muzakky Muzakky (Indonesian Journal of Chemistry, 2010)
Adsorption of Am-241, Cs-137 and Sr-90 radionuclides to bentonite-humic acid immobilized yield have been done. The aims of this study are (1) making of adsorbent materials from resulted immobilization humic acid into bentonite mineral, and it's characterization with spectroscopy infrared and X-ray diffractometer and (2) adsorption of Am-241, Cs-137 and Sr-90 radionuclides into bentonite mineral as adsorbent at various pH. Experiments showed that result of immobilization of bentonite-humic acid were optimum at 100 g bentonite, 60 g humic acid, 0.1 M NaNO3 ionic strength, and 2.5 pH. At the optimum condition bentonite could be bonded by the functional COOH from humic acid maximum equal to 75.2%. Base on infrared spectroscopy and X-ray diffractometer showed that humic acid can immobilized into bentonite to form of bentonite-humic acid alloy. Application of adsorbent bentonite-humic acid immobilized yield to adsorb radionuclides of Am-241, Cs-137 and of Sr-90, showed that can adsorb at the range of pH 3 until 10. The phenomenon adsorption as species radionuclides was predicted by ";;Visual minteq";; software. By each the feeds of radionuclide 0.001 mMol/L, 0.1 M NaNO3 ionic strength and pH 5 showed that bentonite-humic acid can adsorb radionuclides 98.50-99.1% of Am-241, Cs-137, and Sr-90.